2021
DOI: 10.2147/dmso.s310672
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Hemoglobin Glycation Variation Index and Vitamin D in Type 2 Diabetes Mellitus

Abstract: Objective This study aimed to investigate the relationship between hemoglobin glycation variation index (HGI) and vitamin D in patients with type 2 diabetes mellitus (T2DM). Materials and Methods This is a cross-sectional study that recruited 347 patients with T2DM. The subjects were divided into no vitamin D deficiency group (25(OH)D ≥20 ng/mL) and vitamin D deficiency group (25(OH)D < 20 ng/mL). HGI was calculated as the difference between the measured and predicted v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“… 9 , 30 Previously, one of our studies found that T2DM patients with high HGI levels were more susceptible to vitamin D deficiency and that HGI levels were inversely associated with vitamin D levels. 31 This study also found that the NCVN group had lower vitamin D levels and a higher prevalence of vitamin D deficiency than the NCVA group. Vitamin D is a potent neurotrophic factor, and it is involved in the formation of neurotransmitters.…”
Section: Discussionsupporting
confidence: 57%
“… 9 , 30 Previously, one of our studies found that T2DM patients with high HGI levels were more susceptible to vitamin D deficiency and that HGI levels were inversely associated with vitamin D levels. 31 This study also found that the NCVN group had lower vitamin D levels and a higher prevalence of vitamin D deficiency than the NCVA group. Vitamin D is a potent neurotrophic factor, and it is involved in the formation of neurotransmitters.…”
Section: Discussionsupporting
confidence: 57%
“…Because both 1-a-hydroxylase and vitamin D receptors are found in pancreatic beta cells, 25(OH)D has essential functions in the synthesis and release of insulin. 17 Moreover, vitamin D deficiency is independently associated with the high risk of diabetic peripheral neuropathy (DPN) and diabetic nephropathy (DN) in patients with T2DM. It can be a potential predictor of the occurrence and severity of DPN and DN, 18 and it might be responsible for elevated cancer risk development in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the connection between vitamin D levels and glucose metabolism. Vitamin D receptors (VDRs) present in the pancreas, muscles, and adipocytes can influence insulin secretion, glucose uptake, and insulin resistance [26]. The activation of VDRs within pancreatic β cells directly influences the secretion of insulin [27], while in skeletal muscle, it enhances glucose uptake through the SIRT1/IRS1/GLUT4 axis [28].…”
Section: Discussionmentioning
confidence: 99%